2013
DOI: 10.3329/bjar.v37i4.14386
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of parental lines for hybrid development in rice (Oryza sativa L.)

Abstract: Genetic divergence of 40 parental lines comprising 30 restorer and 10 maintainer lines were studied through Mohalanobis's D 2 and principal component analysis for eleven characters. Genotypes were grouped into five different clusters. Cluster V comprised maximum number of genotypes (thirteen) followed by cluster I and II. The inter-cluster distance was maximum between clusters I and V (13.495) indicating wide genetic diversity between these two clusters followed by the distance between cluster I and 11 (9.489)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…For [24] reported both significant positive heterobeltiosis and heterosis for this character, as did Chamundeswari et al [27], Utharasu et al [23] and Parimala et al [8], whereas standard heterosis of similar nature was reported by Dar et al [25], Ramesh et al [28], Gokulakrihnan et al, (2018), Manjunath et al [18] and Mohammad, I. [21,[29][30][31][32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 56%
“…For [24] reported both significant positive heterobeltiosis and heterosis for this character, as did Chamundeswari et al [27], Utharasu et al [23] and Parimala et al [8], whereas standard heterosis of similar nature was reported by Dar et al [25], Ramesh et al [28], Gokulakrihnan et al, (2018), Manjunath et al [18] and Mohammad, I. [21,[29][30][31][32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 56%
“…However with as few as 24 rice varieties, Kunusoth et al, (2015) obtained seven components for 24 traits. Hasan et al, (2012) performed D 2 and PCA analysis in 30 restorer and 10 maintainer lines of rice in which two principal components were derived. In 100 restorer and maintainer lines, 10 clusters were formed in cluster analysis by coefficient of parentage (Wang et al, 2012) of which, the restorer lines further divided into 11 sub clusters.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of diverse parental lines and genetic knowledge of a trait are critical factors in the development of heterotic hybrids. By carefully choosing maintainer and restorer lines based on genetic variation, hybrids with greater yield potential than their parents and traditional check types may be produced (Hasan et al, 2012). Before starting any crop improvement programme or utilising the proper selection strategies, it is essential to understand the nature and scope of genetic variation that governs the inheritance of quantitative traits like yield and its components.…”
mentioning
confidence: 99%